Case Report: Maintenance of Desensitization to Nebulized Colomycin Over 10 Years - Sieber, Justyna; Renner, Sabine; Lakatos-Krepcik, Andrea; Szépfalusi, Zsolt (Frontiers in Pediatrics, 2021)
Drug desensitization can be achieved successfully by gradual drug dose increases in different protocols. Most protocols are designed to obtain temporal tolerance. The data on long-term maintenance of drug tolerance is scarce. Based on an IgE-mediated colomycin allergy we describe the maintenance of drug tolerance to nebulized drug for the period of 10 years in a 15-year-old cystic fibrosis patient, proceeded by successful rush intravenous desensitization protocol. The mechanism of drug tolerance is largely speculative; however, long-term maintenance of it seems achievable by continuous local drug application.